Internalization of stigma among parents of children with autism spectrum disorder in Nigeria: a mixed method study - Aminat Y. Oduyemi (BMC, 2021)
Abstract Background Autism Spectrum disorder (ASD) has uniquely stigmatizing aspects because children with ASD have no physical markers of their condition. Parents are usually blamed and judgment from others is often internalized (felt stigma). Aim This study was conducted to determine knowledge about ASD, negative experiences (enacted stigma), internalization of stigma (felt or self stigma) and its correlates among parents of children with ASD in Lagos, Nigeria. Methods This was a cross-sectional study of 230 parents in Lagos, Nigeria employing mixed-method data collection methods. Quantitative data were collected using a structured interviewer-administered questionnaire and analyzed with Epi- Info™ version 7.0 statistical package. Data were summarized with proportions, mean and standard deviation. Chi square and Spearman’s correlation tests were done, and the level of significance was pre-determined at 5% (p < 0.05). In-depth interviews were also conducted among six parents to further explore the topic. The interviews were analyzed narratively. Results The proportion of mothers and fathers were 175 (76.1%) and 55 (23.9%) respectively. The mean age of respondents was 42 ± 8.5 years. Overall knowledge of ASD was very poor as only 3(1.3%) had good knowledge. Overall, 122(53%) usually had negative experience of parenting a child with ASD (enacted stigma), mothers (17.1%) more than fathers (9.1%). Majority 192(83.5%) internalized stigma. There was a low–moderate correlation between ‘enacted’ stigma and ‘internalized’ stigma (ρ- 0.400, p < 0.001). From in-depth interviews, many parents revealed that their child’s condition had negative effects on the family. Many also recounted negative experience of stigma. Conclusion Overall, parents of children with ASD had poor knowledge of the condition. Majority internalized stigma and this increases with negative treatment from others. Parents should be properly educated about ASD. Community-based education to increase awareness about ASD in addition to encouraging people to show empathy and reduce stigmatizing behaviour towards parents of children with ASD are recommended.